OPTIMIZATION OF DELIVERY MANAGEMENT IN PREGNANT WOMEN WITH PLACENTA PREVIA AND ACCRETA IN WOMEN WITH A SCAR ON THE UTERUS - Olimova, N.Kh.; Matyakubova, S.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Recently, complete or partial placenta previa with signs of accretion along the scar has become the leading cause of haemorrhage in obstetrics. Aim of the study. To develop a scale for predicting the risk of massive haemorrhages taking into account clinical and biochemical markers of placenta previa and placenta accreta in pregnant women with uterine scar, to optimize the interdisciplinary approach to their management on the basis of the obtained results. Material and methods: data for the period from January 2021 to March 2024 on late pregnancies and deliveries with complete placenta previa were used in this work. Results: the total number of deliveries during these years was 15289, of which 44% were by caesarean section, 0.88% of operative deliveries were clearly diagnosed with placenta previa. Among severe complications, 1.72% were acute renal failure and 5.17% of patients had haemorrhagic shock. 8.47% of women presenting to the emergency room with placenta previa were delivered urgently according to vital signs, the remaining 91.52% were transferred for elective surgery. Conclusions: pregnant women with placenta previa and placenta accreta, who should be considered high risk, should be delivered in perinatal centres with qualified staff, adequate blood transfusion facilities and good neonatal resources.